Association Between Proton Pump Inhibitor Use and Biliary Tract Cancer Risk: A Swedish Population‐Based Cohort Study. Issue 4 (13th July 2021) - Kamal, Habiba; Sadr‐Azodi, Omid; Engstrand, Lars; Brusselaers, Nele
Abstract : Background and Aims: Biliary tract cancer is a group of highly aggressive malignant disorders, yet risk factors are poorly understood. In this study, we aim to assess whether prolonged use of proton pump inhibitors (PPIs) increases the risk of incident biliary tract carcinoma in a nation‐wide population‐based cohort in Sweden. Approach and Results: Using nation‐wide registries, we identified all adults who received maintenance PPIs (≥180 days) according to the Swedish Prescribed Drug Register from 2005 through 2012. Data on incident biliary tract cancer were retrieved from the Swedish Cancer, Death and Outpatient Registers. Risk of biliary tract cancer in persons who received PPI treatment was compared with the general population of the corresponding age, sex, and calendar year yielding standardized incidence ratios (SIRs) with 95% CIs. Of 738, 881 PPI users (median follow‐up of 5.3 years), 206 (0.03%) developed gallbladder cancer and 265 (0.04%) extrahepatic and 131 (0.02%) intrahepatic bile duct cancer corresponding to SIRs of 1.58 (95% CI, 1.37‐1.81), 1.77 (95% CI, 1.56‐2.00), and 1.88 (95% CI, 1.57‐2.23), respectively. In sensitivity analyses restricted to persons without a history of gallstones or chronic liver or pancreatic diseases, SIRs were 1.36 (95% CI, 1.17‐1.57) and 1.47 (95% CI, 1.19‐1.80) for extra‐ and intrahepatic duct cancer, respectively. The risk remained higher than the corresponding general population with ≥5 years of PPIs use, ruling out confounding by indication. Conclusions:  In this study, long‐term use of PPIs was associated with an increased risk of gallbladder, intrahepatic, and extrahepatic bile duct cancer compared with the general population.